Quantized vortices in systems with pairing of spatially separated electrons and holes - Shevchenko, S. I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
It is predicted that in systems with pairing of spatially separated electrons and holes the planar vortices, in which the electron-hole pairs rotate in the plane of the structure, can become energy-advantageous in a nonuniform magnetic field. In this case the vortices should form an ordered, though translation-noninvariant, structure.